2017
DOI: 10.1165/rcmb.2016-0252oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Rhinovirus Infection of Epithelial Cells Modulates Airway Smooth Muscle Migration

Abstract: Rationale: Airway remodeling, a characteristic feature of asthma, begins in early life. Recurrent human rhinovirus (HRV) infections are a potential inciting stimulus for remodeling. One component of airway remodeling is an increase in airway smooth muscle cell mass with a greater proximity of the airway smooth muscle cells (ASMC) to the airway epithelium. We asked whether human bronchial epithelial cells infected with HRV produced mediators that are chemotactic for ASMC.Methods: ASMC migration was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…106 Finally, RVs can contribute to airway remodeling by inducing vascular endothelial growth factor, TGF-b, and chemoattractants for airway smooth muscle cells. 107,108 These effects might be more pronounced for RV infections in early life. 109 Thus repeated RV infections that extend to the lower airways could damage the airways and lead to remodeling of airway structures.…”
Section: Mechanisms Linking Rv-induced Wheezing To Asthma Developmentmentioning
confidence: 99%
“…106 Finally, RVs can contribute to airway remodeling by inducing vascular endothelial growth factor, TGF-b, and chemoattractants for airway smooth muscle cells. 107,108 These effects might be more pronounced for RV infections in early life. 109 Thus repeated RV infections that extend to the lower airways could damage the airways and lead to remodeling of airway structures.…”
Section: Mechanisms Linking Rv-induced Wheezing To Asthma Developmentmentioning
confidence: 99%
“…Pooled HBE supernatants were diluted 1:10 in neutrophil resuspension medium. Neutrophil migration over a 1-h period was assessed using a modified Boyden chamber (NeuroProbe, Cabin John, MD) as described (21,31).…”
Section: Neutrophil Isolation and Recruitment Assaymentioning
confidence: 99%
“…Airway epithelial cells are the primary site of RV infection and replication, and release cytokines that orchestrate downstream responses [13][14][15][16] . It has previously been shown that bronchial epithelial cells (BECs) from asthma cases and non-asthma controls have different transcriptional and cytokine responses to RV in cell culture [17][18][19][20][21] .…”
mentioning
confidence: 99%